Acquisition of multiple physiological parameters during physical exercise - Felizardo, Virginie (2019)
This paper describes the experimental method focused on the acquisition of various physiological parameters during different effort levels of physical exercise like walking and running at several velocities. The study involved 57 young and adult people, 43 male and 14 female (24,37±5,96 years), from which 48 were soldiers belonging to the Infantry Regiment n.° 13 (RI13) of the Portuguese Army and 9 were teachers or college students of Sport Sciences, physically active but not competitive. The experimental measures provide a set of information that offers insight about the health status and physical performance of the subjects during exercise. This experimental method procedure is suited for the acquisition of physiological parameters with both the wireless physiological data acquisition systems such as the bioPlux and the respiratory analyzer gas systems such as Cosmed K4b2.The data was collected to allow the definition of a model that will be used to estimate the energy expenditure of a subject using a wireless physiological data acquisition system, which is much more comfortable and suitable to monitor physical exercise in everyday use than the standard method that makes use of a respiratory gas analysis system.